Glycogenic Hepatopathy: Resolution with Minimal Glucose Control - Abhimanyu Chandel; Brittany Scarpato; Jeanette Camacho; Miles McFarland; Shaffer Mok (Case Reports in Hepatology)
We describe a presentation of glycogenic hepatopathy in a poorly controlled type I diabetic patient. As patients with glycogenic hepatopathy often have nonspecific complaints, diagnosis tends to be delayed and laboratory and imaging data are often indistinguishable from nonalcoholic fatty liver disease. Our patient’s diagnosis of glycogenic hepatopathy required a liver biopsy, which demonstrated the characteristic pathology. Her symptoms resolved with minimal alteration to her insulin regimen and only slightly improved glucose control.